2021
DOI: 10.1016/j.cjtee.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on the mental health of young people: A comparison between China and the United Kingdom

Abstract: s Purpose As COVID-19 spreads globally and affects people's health, there are concerns that the pandemic and control policies may have psychological effects on young people (age from 17 to 35 years). This psychological impact might vary in different countries, and thus we compared the prevalence of self-reported psychological distress, loneliness and posttraumatic stress symptoms (PTSS) among young people in the United Kingdom (UK) and China at the beginning of the COVID-19 pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The results were consistent with those of the related study by Xin et al (8). In addition, the result was partially consistent with another study, which showed mental health and loneliness reported by young people were lower in China than that in the United Kingdom during the COVID-19 pandemic (14). On the one hand, this might be the case because the Chinese Spring Festival and winter vacation played a double-buffering role during the outbreak of COVID-19 in China.…”
Section: Discussion College Students' Pandemic Stress Risk Perception...supporting
confidence: 92%
See 2 more Smart Citations
“…The results were consistent with those of the related study by Xin et al (8). In addition, the result was partially consistent with another study, which showed mental health and loneliness reported by young people were lower in China than that in the United Kingdom during the COVID-19 pandemic (14). On the one hand, this might be the case because the Chinese Spring Festival and winter vacation played a double-buffering role during the outbreak of COVID-19 in China.…”
Section: Discussion College Students' Pandemic Stress Risk Perception...supporting
confidence: 92%
“…On the other hand, when facing major public health events, the public's mental health is directly related to their stress and risk perception, but most of the above studies mainly measured anxiety or depression. Therefore, future research should use more comprehensive measures of mental health and explore the causes and determinants of individual mental health during the pandemic (12)(13)(14)(15).…”
Section: Pandemic Stress Risk Perception and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Once again, it is likely that people look for a coping mechanism to reduce anxiety and likely depression symptoms [22] either by pornography and masturbation during lockdown or by casual or paid sex during the post-lockdown phase. However, to some extent, it can also be hypothesized that this lust for sex may reach, in some subjects, the traits of hypersexual behavior characterized by compulsivity and obsession towards sex [79,80] in spite of the potential risks to one's own health; since hypersexuality is a known reaction to trauma [81], this finding would be in agreement with the assumption of COVID-19 as a traumatic event [9][10][11]. Overall, these findings would also explain the return to pre-lockdown levels for queries pertaining to casual or paid sex or for search volume for proerectile treatments following the end of restriction measures.…”
Section: Discussionsupporting
confidence: 65%
“…At the same time, strict lockdown carries high economical costs, with temporary shutdown of many activities and selected work categories being put indefinitely on hold or with citizens being forced to work remotely with difficulties in the family management [8]. Without a shade of doubt, the COVID-19 pandemic and the related containment measures have been identified as traumatic events [9][10][11] that contributed to generate anxiety and stress, conditions having a well-known, negative effect on overall health and well-being [12], and possibly associated with worse outcomes in terms of obesity, cognition, cardiovascular disease, and cancer [13][14][15].…”
Section: Introductionmentioning
confidence: 99%